The Operational Capacity of Healthcare Sector in Handling Covid-19 in Indonesia - Sitti Aminah; Slamet Rahmat Topo Susilo; Yusniah Anggraini (GoAcademica Research & Publishing, 2022)
Indonesia has faced a crisis in handling the Covid-19 pandemic, especially in June and July 2021. It has caused Indonesia placed the highest daily death rate in the world. The study aimed to analyze the level of operational capacity handling the Covid-19 pandemic. The study used a quantitative method, supported by qualitative data sources by literature studies. The data collection was carried out by survey methods in four provinces with the highest active cases in Indonesia. The analysis technique used descriptive statistics. The results of the study show that operational capacity is in the moderate category (66,15). The five indicators of operational capacity are in the moderate category, meaning they are not optimally supporting the handling of Covid-19, namely: the availability of hospital facilities (average score 68), availability of medical devices (average score 67), availability of health workers (average score of 69.22), the capacity to prevent transmission of Covid-9 (average score 62), lastly, the implementation of vaccination (average score 65). The recommendations of the study are: 1) Compile data on the availability of hospital beds according to standard requirements; 2) Improvement of laboratory capacity; 3) Develop a liaison network for producers, donors, and users, supply medical equipment and medicines; 4) Intensify testing and tracing; 5) Evaluating the needs of health workers and setting standards for their safety protection; 6) Increase vaccination targets, especially for the elderly.